Talleres sobre las parábolas del evangelio de san mateo para los jóvenes integrantes del grupo juvenil “Acción Juvenil Franciscana” del Colegio San Francisco de asís de la ciudad de Loja período 2012-2013 - Agila Ramírez, Betty Yomar (2013)
The evaluation and use of the Bible by young people is minimal. Today there is little familiarity with the Gospel. It is a proposal for training and spiritual growth, in light of the Parables of Jesus from the Gospel of Matthew, and bearing in mind some documents of youth ministry for young people to wake up, sit down and make concrete choices made within the Church and society. At first was carried out with the youth group for a survey analysis of their reality, their contribution was very significant because for the process is essential pastoral from reality. The focus for this work, was five parables of Jesus taken from the Gospel of Matthew, which reveals that Good News which is the Kingdom of God. The primary aspect of the parables is the announcement of the reign of God, their characteristics and their values.